Single-energy non-contrast hepatic steatosis criteria applied to virtual non-contrast images: is it still highly specific and positively predictive?. Issue 6 (June 2018) - Haji-Momenian, S.; Parkinson, W.; Khati, N.; Brindle, K.; Earls, J.; Zeman, R.K.
Abstract : Aim: To determine the sensitivity, specificity, and predictive values of single-energy non-contrast hepatic steatosis criteria on dual-energy virtual non-contrast (VNC) images. Materials and methods: Forty-eight computed tomography (CT) examinations, which included single-energy non-contrast (TNC) and contrast-enhanced dual-energy CT angiography (CTA) of the abdomen, were enrolled. VNC images were reconstructed from the CTA. Region of interest (ROI) attenuations were measured in the right and left hepatic lobes, spleen, and aorta on TNC and VNC images. The right and left hepatic lobes were treated as separate samples. Steatosis was diagnosed based on TNC liver attenuation of ≤40 HU or liver attenuation index (LAI) of ≤–10 HU, which are extremely specific and predictive for moderate to severe steatosis. The sensitivity, specificity, and predictive values of VNC images for steatosis were calculated. VNC-TNC deviations were correlated with aortic enhancement and patient water equivalent diameter (PWED). Results: Thirty-two liver ROIs met steatosis criteria based on TNC attenuation; VNC attenuation had sensitivity, specificity, and a positive predictive value of 66.7%, 100%, and 100%, respectively. Twenty-one liver ROIs met steatosis criteria based on TNC LAI. VNC LAI had sensitivity, specificity, and positive predictive values of 61.9%, 90.7%, and 65%, respectively. Hepatic and splenic VNC-TNC deviations did not correlate with one another ( R 2 =0.08), aortic enhancement ( R 2 <0.06) or PWED ( R 2 <0.09). Conclusions: Non-contrast hepatic attenuation criteria is extremely specific and positively predictive for moderate to severe steatosis on VNC reconstructions from the arterial phase. Hepatic attenuation performs better than LAI criteria. VNC deviations are independent of aortic enhancement and PWED. Highlights: Noncontrast hepatic attenuation of less than 40 HU is highly specific and positively predictive for ≥30% steatosis on VNC reconstructions from the arterial-phase. Hepatic attenuation criteria performs better than liver attenuation index criteria on VNC images. VNC deviations do not correlate with the amount of intra-aortic contrast or body habitus (in reconstructions created from the arterial phase of imaging).